# The normal to the curve, ${x^2} + 2xy - 3{y^2} = 0$, at $\left[ {1,1} \right]$

${\text{A}}{\text{.}}$ does not meet the curve again

${\text{B}}{\text{.}}$ meets the curve again in the second quadrant

${\text{C}}{\text{.}}$ meets the curve again in the third quadrant

${\text{D}}{\text{.}}$ meets the curve again in the fourth quadrant

Last updated date: 20th Mar 2023

•

Total views: 305.4k

•

Views today: 8.84k

Answer

Verified

305.4k+ views

**Hint:**Here, we will be using the concept of finding the slope of the normal to any curve and the formula for equation of any line which slope m and passing through a point.

Given equation of the curve is ${x^2} + 2xy - 3{y^2} = 0{\text{ }} \to {\text{(1)}}$

**Complete step-by-step answer:**

Here, we need to first of all find the equation of the normal to the given curve. As, we know that the slope of normal to any curve is $ - \dfrac{{dx}}{{dy}}$ .

Let us differentiate the given equation of curve both sides with respect to x, we get

\[

\dfrac{{d\left( {{x^2} + 2xy - 3{y^2}} \right)}}{{dx}} = 0 \Rightarrow \dfrac{{d\left( {{x^2}} \right)}}{{dx}} + 2\left[ {\dfrac{{d\left( {xy} \right)}}{{dx}}} \right] - 3\left[ {\dfrac{{d\left( {{y^2}} \right)}}{{dx}}} \right] = 0 \Rightarrow 2x + 2\left[ {y\left( {\dfrac{{dx}}{{dx}}} \right) + x\left( {\dfrac{{dy}}{{dx}}} \right)} \right] - 3 \times 2y\left[ {\dfrac{{dy}}{{dx}}} \right] = 0 \\

\Rightarrow 2x + 2y + 2x\left( {\dfrac{{dy}}{{dx}}} \right) - 6y\left( {\dfrac{{dy}}{{dx}}} \right) = 0 \Rightarrow 2\left( {x + y} \right) + 2\left( {\dfrac{{dy}}{{dx}}} \right)\left( {x - 3y} \right) = 0 \Rightarrow 2\left( {\dfrac{{dy}}{{dx}}} \right)\left( {x - 3y} \right) = - 2\left( {x + y} \right) \\

\Rightarrow \left( {\dfrac{{dy}}{{dx}}} \right) = - \dfrac{{2\left( {x + y} \right)}}{{2\left( {x - 3y} \right)}} \Rightarrow \left( {\dfrac{{dy}}{{dx}}} \right) = - \dfrac{{\left( {x + y} \right)}}{{\left( {x - 3y} \right)}} \\

\]

Slope of normal to the given curve$ = - \dfrac{{dx}}{{dy}} = \dfrac{{ - 1}}{{\dfrac{{dy}}{{dx}}}} = \dfrac{{ - 1}}{{\left[ { - \dfrac{{\left( {x + y} \right)}}{{\left( {x - 3y} \right)}}} \right]}} = \dfrac{{\left( {x - 3y} \right)}}{{\left( {x + y} \right)}}$

In order to find the slope of the normal to the given curve at a point $\left[ {1,1} \right]$, let us substitute x=1 and y=1 in the above expression of slope.

Slope of normal to the given curve at $\left[ {1,1} \right]$$ = - \dfrac{{dx}}{{dy}} = \dfrac{{\left( {1 - 3 \times 1} \right)}}{{\left( {1 + 1} \right)}} = \dfrac{{1 - 3}}{2} = - 1$

Also, we know that equation of the line with slope m and passing through any point (${x_1},{y_1}$) is given by $y - {y_1} = m\left( {x - {x_1}} \right)$

Now, equation of the normal with slope of -1 and passing through point $\left[ {1,1} \right]$ is given by

$y - 1 = - 1\left( {x - 1} \right) \Rightarrow y - 1 = - x + 1 \Rightarrow x + y - 1 - 1 = 0 \Rightarrow x + y - 2 = 0{\text{ }} \to {\text{(2)}}$

Now, in order to find out whether this normal meets the given curve at any point other than the given point $\left[ {1,1} \right]$. Let us solve for the common solutions between the curve and the normal.

Equation (2) can be written as $ \Rightarrow x + y - 2 = 0 \Rightarrow x = 2 - y{\text{ }} \to {\text{(3)}}$

Substitute equation (3) in equation (1), we get

${\left( {2 - y} \right)^2} + 2y\left( {2 - y} \right) - 3{y^2} = 0 \Rightarrow 4 + {y^2} - 4y + 4y - 2{y^2} - 3{y^2} = 0 \Rightarrow 4 - 4{y^2} = 0 \Rightarrow {y^2} = 1 \Rightarrow y = \pm 1$

When y=1, equation (3) reduces to $ \Rightarrow x = 2 - y = 2 - 1 \Rightarrow x = 1$

When y=-1, equation (3) reduces to $ \Rightarrow x = 2 - y = 2 - \left( { - 1} \right) \Rightarrow x = 3$

So, the points where the given curve meets with the normal to this curve are (1,1) and (3,-1).

Clearly, apart from point (1,1) the given curve meets the normal to this curve at (3,-1) which lies in the fourth quadrant because in the fourth quadrant x-coordinate is positive and y-coordinate is negative.

**Hence, option D is correct.**

**Note:**In these types of problems, we will simply find the equation for the normal to the given curve at the given point by finding the slope of the normal. Then, we will find the points of intersection of the given curve and normal to the given curve and if any other point appears except the given point that means that the normal meets the curve again else it does not.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE